Migration, gender and sexually transmitted infections among young adults in Lesotho. - Manthata, Goitseone (My University, 2013)
Background This report examined the association and relationship between Migration, Gender and STIs among young adults in Lesotho. To achieve this, the first objective was to understand the historical trans-boundary relationship between Lesotho and South Africa and how it contributed to STIs among young adults in Lesotho. The report then described the relationship between migration and having had any STIs among young adults in Lesotho. After multivariate analysis the association, between gender and having had any STIs among young adults in Lesotho was explored for understanding. Methodology For data analysis, secondary data from the 2009 Lesotho Demographic Health Survey (LDHS) were used. The LDHS is a cross-sectional study, designed to provide estimates of health and demographic indicators at the national level, for urban-rural areas and for each of the ten districts in Lesotho. The sample size used for this report was N=6,270. The statistical methods employed for data analysis were descriptive analysis, to establish the distribution of young adult migrant groups, according to STIs, demographic, socioeconomic and sexual practices. A Chi-square test was done to test for association. And a multivariate analysis was done using the forward selection process, to examine the relationships between STIs, migration, gender and significant variables. Results Migration status was found to have an insignificant (p=0.237) association with STIs. On the other hand, after considering migration status and gender at multivariate level, migration status, specifically urban-non migrants, were found to have a significant (p<0.05) relationship with having had any STIs. Gender was found to have an insignificant (p=0.587) association with having had any STIs and an insignificant (p=0.365) relationship with having had any STIs. However at multivariate level being female was found to be 16% protective against having had any STIs. Conclusion The report found that the relationships between migration status and having had any STIs were closely linked to factors related to gender and social and cultural norms pertaining to sexual behaviour. These influences were reflected in the literature and empirical evidence of this research report.
Keywords: Sexually transmitted diseases--Lesotho.; Young adults--Sexual behavior--Lesotho.; Gender identity--Lesotho.; Lesotho--Emigration and immigration.